Presentation of Pediatric Unintentional Injuries at Rural Hospitals in Rwanda: A Retrospective Study - Irene Bagahirwa; Madeleine Mukeshimana; Teena Cherian; Theoneste Nkurunziza; Ziad El-Khatib; Jean Claude Byiringiro; Loise Ng'ang'a; Emmanuel Rusingiza; Robert Riviello; Gilles Francois Ndayisaba; Bethany L. Hedt-Gauthier (Ubiquity Press, 2020)
Background: Injuries are a leading cause of mortality among children globally, with children in low- and middle-income countries more likely to die if injured compared to children in high-income countries. Timely and high-quality care are essential to reduce injury-related morbidity and mortality. Objectives: This study describes patterns, management, and outcomes of children 0-15 years presenting with unintentional injuries at three district hospitals in rural Rwanda between January 1 and December 31, 2017. Methods: Using a retrospective cross-sectional study design, we assessed the demographic and clinical characteristics, care provided, and outcomes of the children using data extracted from patient medical charts. We describe the patient population using frequencies and proportions as well as median and interquartile ranges. Findings: Of the 449 injured children who sought care at the three rural district hospitals, 66.2% (n = 297) were boys. The main causes of injury were falls (n = 261, 58.1%), burns (n = 101, 22.5%), and road traffic injuries (n = 67, 14.9%). Burns were the most common injury among children aged 0-5 years while falls were the leading injury type among the 5-15 years age group. Vital signs were inconsistently completed ranging between 23.8-89.1% of vital sign items. Of the injured children, 37.0% (n = 166) received surgery at the district hospital, general practitioners performed 80.9% (n = 114) of surgeries, 87.4% (n = 145) of operated patients received no anesthesia, and 69.3% (n = 311) were admitted to the district hospital, while 2.7% (n = 12) were transferred to tertiary facilities for higher-level care. Conclusions: The presentation of child injuries-namely falls, burns, and road traffic accidents-is similar to what has been reported in other sub-Saharan African countries. However, more needs to be done to improve the completion and documentation of vital signs and increase availability of surgical specialists. Finally, targeted strategies to prevent burns and motorcycle-related injuries are recommended prevention interventions for this rural population.